Un corps professionnel renouvelé : les professeurs des universités québécoises francophones entre 1959 et 1976 - Dandurand, Pierre (Canadian Journal of Higher Education, 1989)
At the same time as a new concept of universities was being developed, during the post-war period, a new professionalisation project emerged among Quebec's Francophone university professors, placing scientific research at the centre of university practices which, in order to be accomplished, required changes in university structures. This article attempts to show how, from 1959 onwards, these new conditions came about with more direct State funding of universities and very rapid institutional development along with the bureaucratization of the university system and unionization of professors. By 1976, the end of the period covered by our study, the unionization of professors was achieved and the outline of the movement toward professionalisa- tion characteristic of the 1980's already in place.